The Relationship between PMO and the Level of Adherence to Taking Medication and Completeness of Treatment for Tuberculosis Patients at the UPT Puskesmas Long Me Sangat - Yusnita Florentina; Joko Sapto Pramono; Amiruddin (Formosa Journal of Science and Technology, 2023)
The aim of the research was to determine the relationship between the role of the drug swallowing supervisor (PMO) and the level of compliance with taking medication and completeness of treatment for tuberculosis patients at the UPT Puskesmas Long Me Sangat. This research uses a correlation study design using a cross sectional approach. The test results using the chi-square test obtained a p-value = 0.004 (Medication Adherence) and a p-value = 0.004 (completeness of treatment).